(untitled) (Scientific journal of the Fergana State University, 2023)
In the presented article the scientific significance of organization and implementation of an archaeological expedition on the rapid construction of the Great Fergana Canal (GFC) in 1939. Organizational aspects of the expedition are presented on the basis of archival material from the “Uzkomstaris” fund. There have been given a retrospective of scientific results concerning the towns of the Fergana Valley of the period of the so-called “Muslim renaissance